(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Completion on time with defined cost and quality specified is considered as the important parameter for any successful project. Delays are very severe problem for the construction industry not only in India but all around the world. One of the reasons for cost overrun is the underlying of the other factors which implies the delay in mean time overruns. The main aim and objective of this study is to sort out the important causes of delays within the Indian construction industry so that all stakeholders could have idea about what are the areas that they should give more attention for minimizing delays. These objectives are being completed by implementation of the methodology to identify evaluate the significant factors that causes delays to construction projects.The study exposes that all investors of construction parties are extremely involved in contributing to the reasons of the issues. Recommendations are suggested to minimize the occurrence of these critical factors causing delays considerably. The outcome of the results indicates that all of the parties have some contributions deeply in causing the delays problems due to the overlapping and dynamic nature of construction activities and hardly one could find out whose responsibility lies at the core.